Novel System for Improved Control of Filamentous Microorganisms in Continuous Culture - Brunner, H. (1972)
We describe a system devised to overcome the tendency of fungal mycelium grown in continuous cultures to adhere to the walls and hamper the outflow of the fermentation vessel, with resulting difficulties in attainment of true steadystate conditions.